Peran Koperasi Dalam Mendorong Pengembangan UMKM Di Masyarakat Kota Medan - Dwika, Galuh Citra Sukma; Nurafni, Anggi; Barus, Vivi Aprinilova; Zhafira, Tengku Aiena; Hayati, Fitri (Jurnal Manajemen Akuntansi (JUMSI), 2025)
This study examines the important role of cooperatives in promoting the growth of Micro, Small and Medium Enterprises (MSMEs) in Medan City. Cooperatives serve as a collaborative platform for their members, which in turn improves access to capital, training and marketing. In particular, savings and loan cooperatives are expected to make a significant contribution to the development of MSMEs, while adhering to existing sharia principles. the research method used is descriptive qualitative. the results of this study show that cooperatives have the ability to increase people's income and quality of life through better financial services and training programs for MSME actors. Thus, it can be concluded that cooperatives have a strategic role in empowering MSMEs, but must still pay attention to service quality to meet consumer expectations.